Principal Grasses and Grassland Habitats of Jalpaiguri Division, West Bengal - Chaudhuri, A. B. (Indian Forester, 1960)
In this article an attempt has been made to describe the principal grasses. that foresters encounter in course of their daily duties and to group them into grassland types in relation to their habitats. The Sal forests have become moister due to rigid fire-protection and consequently there has been rapid invasion of evergreen vegetation and, therefore, extensive grasslands or savannah-like formations are completely absent. It is, therefore, very difficult to classify the grasses under definite broad grassland types although an attempt has here been made to classify the most common types. Principal sedges and their habitats have also been described.